2022
DOI: 10.1038/s41405-022-00115-7
|View full text |Cite
|
Sign up to set email alerts
|

“Difficult” dental patients: a grounded theory study of dental staff’s experiences

Abstract: Introduction The “difficult” patient is a well-known and potentially negative character in various care contexts. Objectives This study aimed to generate a conceptual framework explaining the main concerns about “difficult” dental patients, and obtain a deeper understanding of their characteristics, how they affect the dental staff and how the staff think and act in order to manage these patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Even though we considered only the descriptive perspective of the current analysis, it was found that ethical relations with colleagues were a source of a higher level of overall professional satisfaction. In general, excluding interactions with "difficult" dental patients [35,36], multiple lines of evidence have suggested that predictors of satisfaction are greatly connected to factors related to interpersonal relationships (with patients, colleagues, staff) [22,25,26,30,33,34,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Even though we considered only the descriptive perspective of the current analysis, it was found that ethical relations with colleagues were a source of a higher level of overall professional satisfaction. In general, excluding interactions with "difficult" dental patients [35,36], multiple lines of evidence have suggested that predictors of satisfaction are greatly connected to factors related to interpersonal relationships (with patients, colleagues, staff) [22,25,26,30,33,34,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the importance of patient satisfaction as a determinant of healthcare utilization, adherence to treatment, and overall health outcomes. Satisfaction levels are influenced by various factors, including the physician’s communication skills, empathy, and competence, as well as the time spent with patients [ 15 , 16 , 17 ]. Additionally, the organizational aspects of healthcare services, such as accessibility, waiting times, and administrative support, also contribute significantly to patient satisfaction [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a historic perspective it has been common practice within many healthcare professions to refer to such conflicting encounters as encounters with «difficult patients» [ 3 ]. Studies show that the “difficult patient” is also discussed frequently in relation to the dental healthcare setting [ 4 , 5 ], and it appears that certain types of patients, or patient scenarios, are perceived as more stress inducing than others. For instance, when dentists were asked to rank the most intense stressors in their dental practice, anxious patients were ranked fifth among eleven possible, and fear of causing patients pain or unpleasantness was ranked second after time pressure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, failure to successfully identify patients’ anxiety could lead to a breakdown of the therapeutic relationship. Indeed, several studies point to stressful and challenging encounters in dental healthcare as the main arena for when mentalization or similar skill sets play a role [ 4 , 21 , 23 ] , and that the outcomes of the challenging encounters could vary based on how the health professionals choose to approach these encounters [ 4 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation